3(z-5)+6z-1=

Simple and best practice solution for 3(z-5)+6z-1= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(z-5)+6z-1= equation:


3(z-5)+6z-1=0

We simplify the equation to the form, which is simple to understand
3(z-5)+6z-1=0

Reorder the terms in parentheses
+(+3z-15)+6z-1=0

Remove unnecessary parentheses
+3z-15+6z-1=0

We move all terms containing z to the left and all other terms to the right.
+3z+6z=0+15+1

We simplify left and right side of the equation.
+9z=+16

We divide both sides of the equation by 9 to get z.
z=1.77777777778

See similar equations:

| 2x+2x-5=19 | | 10x-130=1 | | 6k-(3k-6)= | | 8-3y=-13 | | 4x+5=41 | | 2+5x=26+5x | | (n-9)*9=27 | | 3(5x-1)=60 | | 2x+7y=24 | | y/5=25 | | (n-3)*2=16 | | log(x-13)=1 | | 4a-3a-2=2(3a-2) | | 7x+17=8x+8 | | 5X+26=X+50 | | n*6=100 | | -5x-35=5 | | y--28=y*32 | | 26-7p=15.50 | | 5x-8=5x-x | | 30n+40= | | -43-15= | | 73=2x+5x+3 | | 9x-10=15+4x | | 3x+6+7x+11= | | 2(3r+5)-32= | | 9x-10=15+4 | | 4b-5+2b=10 | | 4x^2+27x-4=0 | | X-4*y+2=5 | | 500x-0.11=300x+0.47 | | 2x-6=2(x+6) |

Equations solver categories